The Comparison of Demonstrative Learning Method and Computer Assisted Learning on Blood Pressure Measurement at STIKes Guna Bangsa Yogyakarta - Nur Yeti Syarifah (LPPM STIKES Guna Bangsa, 2016)
Rationale: Learning methods in education demand a lecturer not only uses one learning method. It is hoped that the lecturer would deliver an effective and good learning process to his/her students so that the students would achieve better learning results.Therefore, the author is interested to conduct a study“The Comparison of Demonstrative Learning Method and Computer Assisted Learning on Blood Pressure Measurement Guna Bangsa Health College of Yogyakarta in 2012”. Objective: Measuring and comparing study result of the students knowledge, effectiveness and skills) after attending one of methods of learning of demonstrative and CAL on blood pressure measurement. Method:The research samples consist of 76 undergraduates of nursing science which are divided into two groups. This research uses experimental type control time series design which determines the level of the learning skill achieved on measuring the blood pressure, after the students followed demonstrative method of learning and computer assisted learning. The samples are randomized using kind of simple random sampling, which draws members of the population (lottery technique). The instruments used are multiple Choice Question, Checklist and Observation Sheets. The data acquired will be processed and compared using independent t test. Results: Statistically,significant differences on the results of Students attending methods of learning of demonstrative and CAL on blood pressure measurement.Comparison results of measuring the effectiveness of learning using those methods shows that computer assisted learning method resulting in higher mean than the demonstrative method. Conclusion: Demonstrative and Computer Assisted Learning Methods are effective learning methods. They could be used to improve the students’knowledge and skills when well applied.